Altered sensorium unmasking Wernicke–Korsakoff psychosis: A case report (Indian Journal of Case Reports, 2026)
Wernicke–Korsakoff syndrome (WKS) is an acute neuropsychiatric illness produced by chronic deficiency of thiamine (vitamin B1), usually in association with chronic alcoholism. It is characterized by the sudden onset of Wernicke’s encephalopathy (WE) with subsequent chronic Korsakoff’s psychosis if untreated. Here, we describe a 68-year-old man who presented with slurred speech, ataxic gait, memory loss, bewilderment, and disorientation. A past history of alcohol dependence, clinical assessment, elevated liver enzymes, and magnetic resonance imaging findings of mammillary bodies and thalamus involvement led to a Wernicke–Korsakoff psychosis diagnosis. The patient responded well to thiamine replacement therapy and supportive management. The case again emphasizes early identification and treatment of WKS, especially in elderly patients with a history of chronic alcohol use.